Composite hard chrome plating
By adding plate-like alumina particles with a controlled acid and base adsorption ratio to trivalent chromium plating solutions, the composite hard chromium plating film achieves improved adhesion and wear resistance, addressing the issues of non-adhesive portions and peeling in existing films.
Patent Information
- Application Number
- JP2023149179
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-18
- Filing Date
- 2023-09-14
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2042-11-10
AI Technical Summary
Existing composite hard chromium plating films with ceramic particles suffer from low affinity between the ceramic particles and the plating film, leading to non-adhesive portions, peeling of particles, and insufficient hardness and wear resistance.
Incorporating plate-like alumina particles with a specific acid and base adsorption ratio (A/B of 0.5 to 1.5) into trivalent chromium plating solutions, ensuring improved affinity and adhesion between the alumina particles and the plating film.
The composite hard chromium plating film exhibits enhanced hardness and wear resistance, reducing non-adhesive sites and improving the overall quality of the plating film for use in sliding members like piston rings.
Smart Images

Figure 0007670095000002 
Figure 0007670095000003 
Figure 0007670095000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite hard chromium plating film that uses trivalent chromium, and to a sliding member such as a piston ring that is coated with the film. [Background technology]
[0002] In general, chrome plating is widely used as decorative plating because it can maintain metallic luster for a long time due to its excellent corrosion resistance and discoloration resistance. In addition, chrome plating has a high hardness of about 800 to 950 Hv, excellent abrasion resistance, and a low wear coefficient, so it is widely used as hard chrome plating for machine parts, etc. However, the plating solution used for these plating processes contains harmful hexavalent chromium as its main component. Hexavalent chromium is designated as a substance of high concern from the viewpoints of health protection and environmental protection, and there is a demand for the development of chrome plating that does not use hexavalent chromium.
[0003] Chrome plating using less harmful trivalent chromium has been proposed as an alternative to hexavalent chromium. Trivalent chromium plating is used as decorative plating because it has excellent color tone and corrosion resistance when used in relatively thin plating with a thickness of 5 μm or less. However, as hard chrome plating, its abrasion resistance (wear coefficient) is not high enough, and it has not been put to practical use.
[0004] In response to this, a method has been proposed for improving wear resistance in which 10 to 30 volume percent of multiple ceramic particles with excellent wear resistance are contained in the chrome plating (Patent Document 1, Patent Document 2, Patent Document 3).In addition, focusing on the correlation between plating hardness and wear resistance, a method has been proposed for improving hardness by containing plate-like and / or fibrous alumina particles to suppress the expansion and development of cracks during heat treatment (Patent Document 4).
[0005] However, when ceramic particles are used in composite plating, it is known that the particles tend to settle due to their large specific gravity. Therefore, when forming a composite plating film, it is necessary to strongly stir or shake the plating solution in order to prevent the particles from settling.
[0006] However, the composite plating film formed by these methods has a low affinity between the ceramic particles used and the plating film deposited, so that particles fall off from the plating film during processing, resulting in an insufficient amount of ceramic particles to be incorporated, and the formation of the composite plating film is sometimes incomplete due to the fallen particles. In addition, the composite plating film formed has non-adhesive areas between the plating film and the ceramic particles, and does not provide a composite plating film that has both sufficient hardness and wear resistance. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2013-241656 A [Patent Document 2] JP 2016-216833 A [Patent Document 3] JP 2018-159099 A [Patent Document 4] JP 2014-196533 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0008] Therefore, an object of the present invention is to provide a composite hard chromium plating film which, under practical chromium plating conditions, has few defects as a film due to the suppression of non-adhesion areas between the plating film and ceramic particles, and which has excellent hardness and wear resistance, and a sliding member coated with said film. [Means for solving the problem]
[0009] The present inventors have conducted detailed studies on the state of ceramic particles during the formation of a composite hard chrome plating film. As a result of extensive research, they have found that the amount of acid adsorption per surface area A (μmol / m 2 ) and the amount of base adsorbed per surface area B (μmol / m 2 They discovered that by adding plate-shaped alumina particles having a ratio A / B of 0.5 or more and 1.5 or less to chrome plating that uses trivalent chromium as the chromium source, the affinity between the alumina particles and the plating film is ensured, and a plating film in which non-adhesive areas between the particles and the plating metal are suppressed can be obtained, resulting in a plating film that suppresses cracks and has excellent hardness and abrasion resistance.
[0010] That is, the present invention provides a composite hard chromium plating film containing plate-like alumina, the chromium source of the composite hard chromium plating film being trivalent chromium, and the plate-like alumina having an acid adsorption amount A per surface area (μmol / m 2 ) and the amount of base adsorbed per surface area B (μmol / m 2 The present invention relates to a composite hard chromium plating film, characterized in that the ratio A / B of (A) is 0.5 or more and 1.5 or less. Effect of the Invention
[0011] The composite hard chromium plating film of the present invention has excellent affinity between the plating film and the alumina particles, suppressing the occurrence of non-adherent areas, which results in suppression of cracks. The formed film has excellent hardness and wear resistance, and therefore can be suitably used for sliding members such as piston rings. [Brief description of the drawings]
[0012] [Figure 1] 1 is a cross-sectional SEM image of the alumina-dispersed Cr plating film obtained in Example 1. [Diagram 2] 1 is a cross-sectional SEM image of the alumina-dispersed Cr plating coating obtained in Comparative Example 2. [Diagram 3] 1 is a 3D image of polishing marks on the alumina-dispersed Cr plating film obtained in Example 1, observed by a laser microscope. [Figure 4] 1 is a 3D image of polishing marks on the alumina-dispersed Cr plating film obtained in Comparative Example 1, observed with a laser microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] An embodiment of the present invention will be described in detail below. The present invention is not limited to the following embodiment, and can be carried out by making appropriate changes within the scope that does not impair the effects of the present invention.
[0014] <Composite hard chrome plating film> The composite hard chrome plating film is a plating film formed by adding ceramic particles, which are hard particles, to a chrome plating solution and co-depositing with chrome. The ceramic particles are intended to improve the wear resistance of the plating film, and examples of the ceramic particles include alumina, silicon carbide, and diamond. The plating film according to this embodiment contains plate-shaped alumina particles. Since the alumina particles are plate-shaped, when the plating film is formed on the substrate, the alumina particles are oriented along the substrate, thereby reducing damage to the mating material that is the friction counterpart.
[0015] <Chrome plating solution> Chromium plating solutions use trivalent chromium as the chromium source. By using trivalent chromium, it is not necessary to use highly harmful hexavalent chromium. The trivalent chromium plating solution may be prepared according to a known composition, or a commercially available trivalent chromium plating solution may be used. Commercially available solutions include Top Fine Chrome SP, Top Fine Chrome LG (manufactured by Okuno Chemical Industries Co., Ltd.), JCUTRICHROM JTC series (manufactured by JCU Corporation), Envirochrome and CP series (manufactured by MacDermid Performance Solutions Japan Co., Ltd.), etc.
[0016] <Method of forming composite hard chrome plating film> In the method for forming a composite hard chromium plating film of the present invention, a chromium plating bath containing the chromium plating solution and the plate-like alumina particles described below is prepared, and a plating film is formed on an object by a known and commonly used electroplating method.
[0017] <Plate-shaped alumina particles> The "alumina" referred to in this invention is aluminum oxide, and has an acid adsorption capacity A per surface area (μmol / m 2 ) and the amount of base adsorbed per surface area B (μmol / m 2 ) is not particularly limited as long as it satisfies the ratio A / B of the above formula (1), and for example, it may be transition alumina of various crystal forms such as γ, δ, θ, κ, etc., or may contain alumina hydrate in transition alumina. However, it is preferable that the transition alumina is basically of the α crystal form in terms of being more stable.
[0018] In the present invention, "plate-like" refers to an aspect ratio, calculated by dividing the average particle diameter by the thickness, of 2 or more. In this specification, the "thickness of the plate-like alumina particles" is a value measured using a scanning electron microscope (SEM). The "average particle diameter of the plate-like alumina particles" is a value calculated as the volume-based median diameter D50 from the volume-based cumulative particle size distribution measured using a laser diffraction / scattering particle size distribution measuring device.
[0019] The average particle size of the plate-like alumina particles can be appropriately selected depending on the use of the plated object, the thickness of the plating film, etc., but is preferably 0.5 μm or more and 20 μm or less, and particularly preferably 1 μm or more and 10 μm or less. If the average particle size of the plate-like alumina particles is 0.5 μm or more, particle aggregation is suppressed, and if it is 20 μm or less, the area of the alumina particles that function as an insulator is reduced, improving the growth of the plating film, which is preferable.
[0020] The aspect ratio of the plate-like alumina particles can be appropriately selected depending on the application of the plated product, the thickness of the plating film, etc., but is preferably from 5 to 100, and particularly preferably from 10 to 50. When the aspect ratio of the plate-like alumina particles is within the above range, the surface of the formed plating film becomes smooth, the abrasion resistance is excellent, and the aggressiveness to the mating material is suppressed, which is a preferred embodiment.
[0021] The amount of acid adsorption per surface area of plate-shaped alumina particles A (μmol / m 2 ) and the amount of base adsorbed per surface area B (μmol / m 2 The ratio A / B of the amount of acid adsorption per surface area A (μmol / m2) is preferably 0.5 or more and 1.5 or less, and more preferably 0.7 or more and 1.3 or less. When the ratio is within the above range, the affinity between the plating film and the plate-like alumina particles is increased, and non-adhesion areas between the plating film and the plate-like alumina particles are suppressed in the formed plating film. In particular, the amount of acid adsorption per surface area A (μmol / m2) is preferably 0.5 or more and 1.5 or less, and particularly preferably 0.7 or more and 1.3 or less. When the ratio is within the above range, the affinity between the plating film and the plate-like alumina particles is increased, and non-adhesion areas between the plating film and the plate-like alumina particles are suppressed in the formed plating film. 2 ) is 0.5 μmol / m 2 3.5 μmol / m or more 2 It is more preferable for the thickness to be not more than 100 nm from the viewpoint of adhesion to the plating film after the film formation.
[0022] Although it has not been fully elucidated how the amount of acid and base adsorbed per surface area of plate-like alumina particles affects the adhesion between the alumina particles and the plating film, the following hypothesis is conceivable. In general, it is believed that the amount of acid adsorption per surface area of a particle reflects the surface potential of the particle. In other words, particles with a high acid adsorption value are more negatively charged particles. When applying voltage to a solution immersed in positive and negative electrodes, such as in electroplating, negatively charged particles basically migrate toward the positive electrode, but negatively charged particles are easily incorporated into the plating film formed on the negative electrode side by stirring and shaking the plating solution.
[0023] On the other hand, in a strong acidic solution such as a trivalent chromium plating solution, negatively charged particles attract cations and become positively charged colloidal particles. For example, the zeta potential of general ceramic particles is positive. The zeta potential of commercially available alumina particles, which are said to be negatively charged, is about +20mV in a pH 2 solution. In this case, the metal cations are accumulated in layers on the negative electrode surface where the plating film is deposited due to the electrode potential, and even if the positively charged colloidal particles can approach, they have poor affinity with the layer of cations. Through this state, the metal cations are reduced while incorporating the ceramic particles, and the plating film is formed. Based on the above background, it was thought that colloidal particles with low zeta potential can be formed in a low pH range, i.e., particles with a low acid adsorption amount per surface area are suitable for ceramic particle composite chrome plating.
[0024] Furthermore, the co-deposition mechanism of composite plating is presumed to be a mechanism in which metal ions and ceramic particles are individually deposited on the negative electrode as described above, as well as a mechanism in which metal ions are adsorbed to ceramic particles dispersed in the plating, forming a composite and then depositing on the negative electrode. In this case, alumina particles with a large amount of acid adsorption form positively charged colloidal particles in a strong acidic solution, and therefore have a low affinity with metal ions, and are presumed to repel metal ions both in the plating solution and on the negative electrode, and deposit without sufficient adhesion to each other. On the other hand, alumina particles with a large amount of base adsorption do not form positively charged colloidal particles, that is, have a low affinity with metal ions in the first place, and are presumed to deposit without sufficient adhesion to metal ions both in the plating solution and on the negative electrode. Therefore, it is presumed that the more alumina particles are not biased in the amount of acid or base adsorption, the more the decrease in affinity with metal ions is suppressed, the relatively higher the adhesion is, and the less likely non-adhesive areas are to occur between the plating film and the alumina particles. From these findings, it was concluded that in order to suppress the occurrence of non-adherent sites, not only the acid adsorption amount of the alumina particles used but also the base adsorption amount is important.
[0025] <Method of manufacturing plate-like alumina particles> The method for producing the plate-like alumina particles is not particularly limited, and known and commonly used techniques such as a hydrothermal method and a flux method can be appropriately applied. 2 ) and the amount of base adsorbed per surface area B (μmol / m 2 From the viewpoint of suitably controlling alumina particles in which the ratio A / B of (A) is 0.5 or more and 1.5 or less, a production method based on a flux method using a molybdenum compound and a shape control agent can be preferably applied.
[0026] More specifically, a preferred method for producing platelet-shaped alumina particles comprises the step of calcining an aluminum compound in the presence of a molybdenum compound and a shape control agent.
[0027] [Firing process] The calcination step is a step of calcining an aluminum compound in the presence of a molybdenum compound and a shape control agent.
[0028] (Aluminum Compounds) The aluminum compound is a raw material for the plate-like alumina particles used in the present invention, and is not particularly limited as long as it becomes alumina upon heat treatment. For example, aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition alumina (γ-alumina, δ-alumina, θ-alumina, etc.), α-alumina, mixed alumina having two types of crystal phases, etc. can be used, and the physical form, such as the shape, particle size, specific surface area, etc., of these aluminum compounds as precursors is not particularly limited.
[0029] According to the flux method described below, the shape of the plate-like alumina particles is hardly influenced by the shape of the raw material aluminum compound, so that any shape, such as a sphere, an amorphous shape, an aspected structure (wire, fiber, ribbon, tube, etc.), or a sheet, can be suitably used.
[0030] Similarly, the particle size of the aluminum compound is hardly reflected in the plate-like alumina particles according to the flux method described below, so that solid aluminum compounds having sizes ranging from several nm to several hundred μm can be suitably used.
[0031] The specific surface area of the aluminum compound is not particularly limited. Since molybdenum acts effectively, a larger specific surface area is preferable, but by adjusting the firing conditions and the amount of molybdenum used, aluminum compounds with any specific surface area can be used as a raw material.
[0032] (shape control agent) In order to form plate-like alumina particles suitable for the present invention, it is more preferable to use a shape control agent, which not only affects the surface properties of the produced alumina particles, but also promotes the growth of plate-like alumina crystals by calcining the alumina compound in the presence of molybdenum.
[0033] The state in which the shape control agent is present is not particularly limited as long as it can contact the aluminum compound. For example, a physical mixture of the shape control agent and the aluminum compound, or a complex in which the shape control agent is present uniformly or locally on the surface or inside of the aluminum compound can be suitably used.
[0034] The shape control agent may be added to the aluminum compound, or may be contained in the aluminum compound as an impurity.
[0035] The type of shape control agent is not particularly limited as long as it can suppress the selective adsorption of molybdenum oxide to the
[0113] face of α-alumina during high-temperature firing in the presence of a molybdenum compound and form a plate-like shape. It is preferable to use a metal compound other than a molybdenum compound and an aluminum compound in terms of a higher aspect ratio, better dispersibility, and better productivity. Specific examples of shape control agents include silicon atoms, sodium atoms, germanium atoms, and potassium atoms, or compounds thereof, but the shape control agent contained in the present invention is not limited to the above elements and compounds.
[0036] The silicon atom or silicon compound is not particularly limited, and known compounds can be used. Specific examples include artificially synthesized silicon compounds such as metal silicon, organic silane, silicon resin, silica fine particles, silica gel, mesoporous silica, SiC, and mullite; and natural silicon compounds such as biosilica. Among these, it is preferable to use organic silane, silicon resin, and silica fine particles from the viewpoint of forming a more uniform composite or mixture with the aluminum compound. The silicon atom or silicon compound may be used alone or in combination of two or more kinds.
[0037] The shape of the silicon atom or silicon compound is not particularly limited, and for example, a sphere, an amorphous shape, an aspected structure (wire, fiber, ribbon, tube, etc.), a sheet, etc. can be suitably used.
[0038] The amount of silicon atom or silicon compound used is not particularly limited, but is preferably 0.0001 to 1 mol, and more preferably 0.001 to 0.5 mol, per mol of aluminum metal in the aluminum compound. When the amount of silicon atom or silicon compound used is within the above range, it is preferable because plate-like alumina particles having a high aspect ratio and excellent dispersibility are easily obtained.
[0039] In particular, when silicon atoms or silicon compounds are used, it is preferable to form mullite partially on the alumina surface of the final product from the viewpoint of adhesion between the filler and the plating.
[0040] The sodium atom or sodium compound is not particularly limited, and known compounds can be used. Specific examples of sodium atoms or sodium compounds include sodium carbonate, sodium molybdenum, sodium oxide, sodium sulfate, sodium hydroxide, sodium nitrate, sodium chloride, metallic sodium, and the like. Among these, it is preferable to use sodium carbonate, sodium molybdate, sodium oxide, and sodium sulfate from the viewpoint of industrially easy availability and ease of handling. The sodium atom or sodium compound may be used alone or in combination of two or more kinds.
[0041] The shape of the sodium atom or sodium compound is not particularly limited, and for example, a sphere, an amorphous shape, an aspected structure (wire, fiber, ribbon, tube, etc.), a sheet, etc. can be suitably used.
[0042] The amount of sodium atoms or sodium compound used is not particularly limited, but is preferably 0.0001 to 2 mol, and more preferably 0.001 to 1 mol, per mol of aluminum metal in the aluminum compound. When the amount of sodium or the compound containing sodium atoms used is within the above range, it is preferable because plate-like alumina particles having a high aspect ratio and excellent dispersibility are easily obtained.
[0043] The germanium atom or germanium compound is not particularly limited, and known ones can be used. Specific examples of the germanium atom or germanium compound include germanium metal, germanium dioxide, germanium monoxide, germanium tetrachloride, and organic germanium compounds having a Ge-C bond. The germanium atom or germanium compound may be used alone or in combination of two or more kinds.
[0044] The shape of the germanium atom or germanium compound is not particularly limited, and for example, a sphere, an amorphous shape, an aspected structure (wire, fiber, ribbon, tube, etc.), a sheet, etc. can be suitably used.
[0045] The potassium atom or potassium compound is not particularly limited, but includes potassium chloride, potassium chlorite, potassium chlorate, potassium sulfate, potassium hydrogen sulfate, potassium sulfite, potassium hydrogen sulfite, potassium nitrate, potassium carbonate, potassium hydrogen carbonate, potassium acetate, potassium oxide, potassium bromide, potassium bromate, potassium hydroxide, potassium silicate, potassium phosphate, potassium hydrogen phosphate, potassium sulfide, potassium hydrogen sulfide, potassium molybdate, potassium tungstate, etc. In this case, the potassium compound includes isomers. Among these, it is preferable to use potassium carbonate, potassium hydrogen carbonate, potassium oxide, potassium hydroxide, potassium chloride, potassium sulfate, or potassium molybdate, and it is more preferable to use potassium carbonate, potassium hydrogen carbonate, potassium chloride, potassium sulfate, or potassium molybdate. The potassium compounds described above may be used alone or in combination of two or more kinds.
[0046] (Molybdenum Compounds) As described later, the molybdenum compound functions as a flux for the growth of α-crystals of alumina at relatively low temperatures. The molybdenum compound is not particularly limited, but may be molybdenum oxide or a compound containing an acid radical anion (MoOx n-) in which molybdenum metal is bonded to oxygen.
[0047] The compound containing the acid radical anion (MoOx n-) is not particularly limited, but may be molybdic acid, sodium molybdate, potassium molybdate, lithium molybdate, HPMo 12 O 40 , H3SiMo 12 O 40 , NH4Mo7O 12 , molybdenum disulfide, etc.
[0048] The molybdenum compound may contain silicon atoms and / or silicon compounds and / or potassium compounds, and in this case, the molybdenum compound containing the silicon atoms and / or silicon compounds and / or potassium compounds serves as both a flux agent and a shape control agent.
[0049] Among the above molybdenum compounds, it is preferable to use molybdenum oxide from the viewpoint of cost. The above molybdenum compounds may be used alone or in combination of two or more kinds.
[0050] The amount of the molybdenum compound used is not particularly limited, but is preferably 0.01 to 3.0 mol, more preferably 0.03 to 0.7 mol, per mol of aluminum metal in the aluminum compound. When the amount of the molybdenum compound used is within the above range, it is preferable because plate-like alumina particles having a high aspect ratio and excellent dispersibility are easily obtained.
[0051] (Firing) The firing method is not particularly limited, and can be performed by a known, commonly used method. When the firing temperature exceeds 700°C, the aluminum compound reacts with the molybdenum compound to form aluminum molybdate. Furthermore, when the firing temperature reaches 900°C or higher, the aluminum molybdate decomposes, and the shape control agent acts to form plate-like alumina particles. The plate-like alumina particles can be obtained by incorporating the molybdenum compound into the aluminum oxide particles when the aluminum molybdate decomposes to form alumina and molybdenum oxide.
[0052] In addition, the state of the aluminum compound, the shape control agent, and the molybdenum compound during firing is not particularly limited, and it is sufficient that the molybdenum compound and the shape control agent are present in the same space where they can act on the aluminum compound. Specifically, they may be simply mixed by mixing the powders of the molybdenum compound, the shape control agent, and the aluminum compound, mechanically mixed using a grinder, or mixed using a mortar, or may be mixed in a dry or wet state.
[0053] There is no particular limitation on the firing temperature conditions, and the firing temperature is appropriately determined depending on the average particle size, aspect ratio, etc. of the target plate-like alumina particles. Generally, the firing temperature is set to a maximum temperature of 900°C or higher, which is the decomposition temperature of aluminum molybdate (Al2(MoO4)3).
[0054] The calcination temperature can be as high as over 2000°C, but even at temperatures below 1600°C, which are significantly lower than the melting point of α-alumina, it is possible to form α-alumina with a high α-crystallization rate and a high aspect ratio in a plate-like shape regardless of the shape of the precursor.
[0055] When the maximum firing temperature is 900°C to 1600°C, plate-like alumina particles having a high aspect ratio and an α-crystallization rate of 90% or more can be formed efficiently at low cost. Firing at a maximum temperature of 950°C to 1500°C is more preferable, and firing at a maximum temperature in the range of 980°C to 1400°C is most preferable.
[0056] Regarding the firing time, it is preferable that the time required to raise the temperature to the predetermined maximum temperature is within the range of 15 minutes to 10 hours, and that the holding time at the firing maximum temperature is within the range of 5 minutes to 30 hours. In order to efficiently form plate-like alumina particles, it is more preferable that the firing holding time is about 10 minutes to 15 hours. By selecting conditions of a maximum temperature of 1000 to 1400°C and a firing holding time of 10 minutes to 15 hours, dense α-crystal plate-like alumina particles are easily obtained without being easily agglomerated.
[0057] The firing atmosphere is not particularly limited as long as the effects of the present invention can be obtained. For example, an oxygen-containing atmosphere such as air or oxygen, or an inert atmosphere such as nitrogen or argon is preferable, and an air atmosphere is more preferable when cost is taken into consideration.
[0058] The calcination apparatus is not necessarily limited, and a so-called calcination furnace can be used. The calcination furnace is preferably made of a material that does not react with the sublimated molybdenum oxide, and it is preferable to use a highly airtight calcination furnace so as to efficiently utilize the molybdenum oxide.
[0059] [Molybdenum removal process] The method for producing plate-like alumina particles may further include, after the firing step, a molybdenum removal step of removing at least a portion of the molybdenum, as necessary.
[0060] As described above, since molybdenum sublimes during firing, the molybdenum content in the plate-like alumina particles can be controlled by controlling the firing time, firing temperature, etc.
[0061] Molybdenum may adhere to the surface of the plate-like alumina particles, and the molybdenum can be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, or an acidic aqueous solution.
[0062] In this case, the molybdenum content can be controlled by appropriately changing the concentrations and amounts of water, ammonia aqueous solution, sodium hydroxide aqueous solution, and acidic aqueous solution used, as well as the cleaning locations and cleaning times.
[0063] Furthermore, by appropriately adjusting the concentration of the washing solution used in this step, the amount used, and the washing time, the amount of acid and base adsorbed per surface area of the alumina particles can be further controlled.
[0064] [Crushing process] The calcined product may not satisfy the particle size range suitable for the present invention due to aggregation of the plate-like alumina particles. Therefore, the plate-like alumina particles may be pulverized as necessary so as to satisfy the particle size range suitable for the present invention. The method for pulverizing the calcined product is not particularly limited, and a conventionally known pulverization method such as a ball mill, a jaw crusher, a jet mill, a disk mill, a spectromill, a grinder, or a mixer mill can be applied.
[0065] [Classification process] Furthermore, the plate-like alumina particles may be preferably classified to adjust the average particle size to a suitable size for the present invention. "Classification" refers to an operation of grouping particles according to their size. Classification may be either wet or dry, but from the viewpoint of productivity, dry classification is preferred. Dry classification includes classification by sieve, as well as wind classification, which classifies based on the difference between centrifugal force and fluid drag force. From the viewpoint of classification accuracy, wind classification is preferred, and can be performed using a classifier such as an air classifier using the Coanda effect, a swirling air classifier, a forced vortex centrifugal classifier, or a semi-free vortex centrifugal classifier. The above-mentioned pulverization process and classification process can be performed at any necessary stage, including before and after the organic compound layer formation process described later. Depending on the presence or absence of these pulverization and classification and the selection of the conditions for them, for example, the average particle size of the obtained plate-like alumina particles can be adjusted.
[0066] The plate-like alumina particles with little or no aggregation are preferred from the viewpoint of easily exerting their inherent properties, being more easily handled, and being more dispersible when dispersed in a dispersion medium. In the method for producing plate-like alumina particles, if the above-mentioned pulverization step or classification step is not performed and the plate-like alumina particles with little or no aggregation are obtained, it is not necessary to perform the above steps, and the plate-like alumina particles with the desired excellent properties can be produced with high productivity, which is preferred. EXAMPLES
[0067] The present invention will now be described in detail with reference to examples and comparative examples, in which "parts" and "%" are by mass unless otherwise specified. A composite hard chromium plating film was formed under the conditions shown below, and the obtained plating film was measured and evaluated under the conditions shown below.
[0068] <Evaluation of plating film thickness> The cross section of the prepared sample was observed under a microscope, and the film thickness was measured.
[0069] <Measurement of plating film hardness> The obtained plating film was measured using a Shimadzu Dynamic Ultra Micro Hardness Tester DUH211Y (manufactured by Shimadzu Corporation) under a load of 100 gf×14 sec.
[0070] <Body abrasion test of plating film> The wear coefficient and polishing marks of the obtained plating film were evaluated using a Tribometer (manufactured by CSM Instruments). SUJ2 (ball shape, dimension 9.00 mm) was used as the opposing material for friction. The measurement conditions were a contact load of 2.00 N, friction speed of 5.00 cm / s, and friction time of 600 seconds. The polishing marks were evaluated by 3D observation of the polishing marks after measurement using a laser microscope, and were evaluated as "good" if the surface was not depressed, and "x" if it was depressed.
[0071] <Adhesion between plating and filler> The cross section of the prepared sample was observed by SEM. As a result of the observation, it was visually confirmed whether there was a gap between the plating and the filler, and if no gap was observed, it was evaluated as "Good", and if a gap was observed, it was evaluated as "Poor".
[0072] (Synthesis Example 1) Synthesis of plate-like alumina particles 50 g of aluminum hydroxide (manufactured by Nippon Light Metal Co., Ltd., average particle size 12 μm), 0.65 g of silicon dioxide (manufactured by Kanto Chemical Co., Ltd., special grade), and molybdenum trioxide (manufactured by Taiyo Koko Co., Ltd.) were mixed. The mixture was mixed in a mortar with 1.72 g of 1,200°C (manufactured by Sigma-Aldrich Co., Ltd.) to obtain a mixture. The mixture was placed in a crucible and heated to 1200°C at 5°C / min in a ceramic electric furnace, and then fired at 1200°C for 10 hours. The temperature was then lowered to room temperature at 5°C / min, and the crucible was removed to obtain 34.2 g of a light blue powder. The powder was crushed in a mortar until it passed through a 106 μm sieve. The light blue powder obtained was then dispersed in 150 mL of 0.5% ammonia water, and the dispersion was stirred at room temperature (25 to 30°C) for 0.5 hours. The ammonia water was then removed by filtration, and the molybdenum remaining on the particle surface was removed by washing with water and drying, obtaining 33.5 g of a light blue powder. The obtained powder was confirmed to have a plate-like shape by SEM observation, with very few aggregates, and to be a plate-like particle with excellent handleability. Furthermore, when an XRD measurement was performed, a sharp peak scattering due to α-alumina appeared, and no alumina crystal peaks other than the α crystal structure were observed, confirming that the particles were plate-like alumina particles with a dense crystal structure. The α conversion rate was 99% or more (almost 100%). Furthermore, the results of fluorescent X-ray quantitative analysis confirmed that the obtained particles contained 0.8% molybdenum in terms of molybdenum trioxide and 1.9% silicon in terms of silicon dioxide.
[0073] <Measurement of acid adsorption amount of alumina particles> The amount of acid adsorption of the alumina particles was measured using a potentiometric titration COM-1700 (Hiranuma Sangyo Co., Ltd.). 15 mL of 0.001 mol / L p-toluenesulfonic acid (PTSA) / n-propyl acetate (NPAC) solution was added to 1 g of alumina particles and mixed with a planetary stirrer (2000 rpm, 3 minutes). The alumina particles were then allowed to settle by centrifugation (8000 rpm, 20 minutes). 10 mL of the supernatant was taken and subjected to potentiometric titration to measure the amount of unadsorbed acid in the supernatant solution. The amount of acid adsorption to the alumina particles was calculated by subtracting the amount of unadsorbed acid from the amount of acid added. The amount of acid adsorption per surface area A was 2.5 μmol / m 2 It was.
[0074] <Measurement of base adsorption amount of alumina particles> The amount of base adsorption was measured for the alumina particles using a potentiometric titration COM-1700 (Hiranuma Sangyo Co., Ltd.). 15 mL of 0.001 mol / L tetrabutylammonium hydroxide (TBAH) / NPAC solution was added to 1 g of alumina particles and mixed with a planetary stirrer (2000 rpm, 3 minutes). The alumina particles were then allowed to settle by centrifugation (8000 rpm, 20 minutes). 10 mL of the supernatant was taken and subjected to potentiometric titration to measure the amount of unadsorbed base present in the supernatant solution. The amount of base adsorption to the alumina particles was calculated by subtracting the amount of unadsorbed base from the amount of added base. The amount of base adsorption per surface area B was 2.3 μmol / m 2 It was.
[0075] (Specific surface area measurement: BET method) The specific surface area can be determined as the surface area per 1 g of plate-like alumina particles measured by the nitrogen gas adsorption / desorption method using the BET method, and examples thereof include JIS Z 8830: BET one-point method (adsorption gas: nitrogen). More specifically, a sample of alumina particles was pretreated at 300°C for 3 hours, and the specific surface area of the pretreated sample was measured using a TriStar3000 manufactured by Micromeritics. The specific surface area was 1.7 m 2 / g.
[0076] (Measurement of average particle size L) The median diameter D50 (μm) of the plate-like alumina particles obtained in Synthesis Example 1 was determined using a laser diffraction particle size distribution analyzer HELOS (H3355) & RODOS (manufactured by Japan Laser Co., Ltd.) under conditions of a dispersion pressure of 3 bar and a suction pressure of 90 mbar, and was taken as the average particle diameter L (μm). The average particle diameter L was 9.5 μm.
[0077] (Measurement of average thickness D) The thickness of 50 pieces of the above sample was measured using a scanning electron microscope (SEM), and the average value was used as the average thickness D (μm). The average thickness D was 0.63 μm.
[0078] The aspect ratio L / D of the plate-like alumina particles was calculated using the following formula. The aspect ratio L / D was 15.
[0079] (Aspect ratio L / D) Aspect ratio = average particle size L of plate-shaped alumina particles / average thickness D of plate-shaped alumina particles
[0080] The filler used in Comparative Example 1 was also evaluated in the same manner with respect to the acid and base adsorption amounts per surface area, the average particle diameter L, the average thickness D, and the aspect ratio L / D.
[0081] The alpha conversion rate and Mo content of the plate-like alumina particles obtained in Synthesis Example 1 were analyzed by the following methods.
[0082] (Analysis of Mo content in plate-shaped alumina particles) Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), about 70 mg of the prepared sample was placed on filter paper and covered with PP film for composition analysis. The amount of molybdenum determined from the XRF analysis results was calculated as molybdenum trioxide (mass%) relative to 100% by mass of the plate-like alumina particles.
[0083] (Analysis of Alpha Conversion Rate of Plate-shaped Alumina Particles) The prepared sample was placed on a measurement sample holder with a depth of 0.5 mm, and packed flat with a constant load. It was then set in a wide-angle X-ray diffractometer (Rigaku Corporation, Rint-Ultma) and measured under the conditions of Cu / Kα radiation, 40 kV / 30 mA, scan speed of 2 degrees / min, and scan range of 10 to 70 degrees. The α conversion rate was calculated from the ratio of the strongest peak heights of α-alumina and transition alumina.
[0084] Example 1 The plate-like alumina of Synthesis Example 1 was added at a concentration of 20 g / L to a commercially available trivalent chromium plating solution, Top Fine Chrome LG (manufactured by Okuno Chemical Industries Co., Ltd.). A cleaned iron plate was immersed in the plating bath, and a current density of 20 A / dm was applied while stirring the plating bath, with the iron plate as the negative electrode and the counter electrode as the positive electrode. 2A composite hard chrome plating process was performed with a plating bath temperature of 35°C to 40°C and an irradiation time of 40 minutes to form a composite hard chrome plating film with a thickness of approximately 10 μm on the steel plate. The obtained composite hard chrome plating film was evaluated for adhesion between the plating film and the filler, and for polishing marks (Fig. 1, Fig. 3).
[0085] Comparative Example 1 A composite hard chromium plating film having a thickness of about 10 μm was formed on an iron plate in the same manner as in Example 1, except that commercially available plate alumina particles YFA10030 (manufactured by Kinsei Matec Co., Ltd.) were used as the plate alumina particles. The adhesion between the plating film and the filler and the polishing marks of the obtained composite hard chromium plating film were evaluated (FIG. 4).
[0086] Comparative Example 2 Except for not adding the plate-like alumina particles, a chromium plating film having a thickness of about 10 μm was formed (on an iron plate) in the same manner as in Example 1. The adhesion between the plating film and the filler and the polishing marks of the obtained composite hard chromium plating film were evaluated (FIG. 2).
[0087] [Table 1] TIFF0007670095000001.tif43140
Claims
1. A chrome plating solution containing trivalent chromium as a chromium source and an acid adsorption amount A per surface area (μmol / m 2 ) and the amount of base adsorbed per surface area B (μmol / m 2 and a ratio A / B of 0.5 or more and 1.5 or less of plate-like alumina particles.
2. The acid adsorption amount A of the plate-like alumina particles is 0.5 μmol / m 2 3.5 μmol / m or more 2 2. The chromium plating bath according to claim 1, wherein:
3. 3. The chromium plating bath according to claim 1, wherein the plate-like alumina has an average particle size of 1 μm or more and 20 μm or less and an aspect ratio of 5 or more and 100 or less.
Citation Information
Patent Citations
Production of composite dispersive particles and composite plating method
JP1989246398A
Polymer coated fine alumina particles
JP1993148691A
Chromium plated article and chromium plating film
JP2013241656A
Composite hard chromium plating film and sliding member coated with the same
JP2014196533A
Chromium plated article and chromium plated film
JP2016216833A